Are happy managers more productive? - Hosie, Peter; Sevastos, Peter (2005)
Decades of research have failed to establish a strong link between managers' job satisfaction and performance. Despite support in the literature to suggest that a relationship exists between job satisfaction and managers' performance the empirical evidence to support this proposition is mixed. A seminal question in psychology and management is revisited the 'happy managers productive worker' thesis, by investigating the impact of job-related affective well-being and intrinsic job satisfaction on Australian managers performance. Survey items were derived from the literature and administered to managers from Western Australian organizations using self report on established affective well-being and intrinsic job satisfaction scales. An empirical methodology was used to test the hypotheses. Managers' contextual and task performance scales were developed through from the literature and confirmatory factor analysis. A measurement model of managers' performance using supervisory ratings was tested and confirmed to be multivariate and consist of eight-dimensional construct of performance. Canonical correlation and hierarchical multiple regression were used to analyze the linear combination of managers' affective well-being and job satisfaction with their performance. Indicators of affective well-being and intrinsic job satisfaction were found to predict dimensions of managers contextual and task performance.